Da'wah Regarding Human Rights in the Implementation of Workers' Rights in Islam: A Study of Hadith Bukhari number 1930 from the Muhaddist's View - Noor Hamid; Damanhuri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Qur’an and Al-Hadith are the sources of the concept of Islamic work ethics. Islam teaches that hard work can be forgiven for sins and there is nothing better than eating the fruits of one's work. Hadith Bukhari Number 1930 states that: